Agrobacterium‐mediated transformation of yeast using a vir binary vector system - Kiao Huio Yap; Shu Ting Chang; Wai Keat Toh; Pek Chin Loh; Boon Hoe Lim; Khomaizon Abdul Kadir Pahirulzaman; Chai-Ling Ho; Hann Ling Wong (Universitas Gadjah Mada, 2025)
Agrobacterium‐mediated transformation (AMT) is a widely used genetic engineering tool for generating transgenic plants for crop improvement and functional genomics. Beyond plants, AMT has been successfully applied to non‐plant organisms, further expanding its utility. Given their broad applications, enhancing AMT systems to improve their usability, simplicity, and efficiency is highly desirable. In this study, we developed a novel AMT system, the vir binary vector system, comprising the following core components: the binary vector pG103‐GDE‐1 and the miniaturized helper tumor‐inducing (Ti) plasmid pRIDE101, together with the auxiliary replication helper plasmid pSoup. Yeast was used as a model organism to evaluate its functionality in stable transformation, with the neomycin phosphotransferase II (NptII) gene serving as a selectable marker. The system’s functionality was assessed by comparing its transformation frequency to that of the widely used pGWB1 binary vector system. The results demonstrate that the vir binary vector system achieved a trans‐ formation frequency of 0.76 × 10‐6, approximately 75 percent of that of pGWB1 (1.01 × 10‐6). Polymerase chain reaction (PCR) analyses confirmed the presence of the transgene in yeast transformants. These findings validate the functionality of the vir binary vector system and highlight the need for further optimization to enhance its efficiency for broader app